Reshaping the Economy? Local Reallocation Effects of Place-Based Policies - Sarah Fritz; Catherine van der List (CESifo GmbH, 2025)
We study the effects of place-based policies on aggregate productivity using administrative data on projects co-financed by the EU in Italy linked to balance sheet data. We exploit quasi-experimental variation in funding for a large place-based policy stemming from measurement error in regional GDP estimates. Results show that the policy likely decreases productivity. Decompositions reveal that aggregate declines are driven by reallocation of labor to low-productivity firms. Mechanism analysis using firm-level event studies reveals that negative reallocation effects are caused by high-productivity firms taking up the funds and subsequently becoming more liquidity constrained, leading to slowdowns in employment growth.
Keywords: R11; R58; J23; 330; place-based policy; productivity; EU cohesion policy